2018
DOI: 10.1061/(asce)me.1943-5479.0000614
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior in Construction Megaprojects

Abstract: In construction megaprojects, contractors and other participating entities sometimes go beyond what is stipulated in their contract and take initiatives that are irrational in pursuit of short-term economic benefit. This type of citizenship behavior is often observed in many construction megaprojects. However it has not been widely researched, and little is known about organizational citizenship behavior (OCB) and its characteristics in this field. This paper presents an overview of participating entities' OCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 58 publications
(41 reference statements)
1
45
0
Order By: Relevance
“…However, there is rather limited literature on OCB in the context of megaprojects. Similar to the definition of OCB in organizational areas, OCB in the megaprojects field can be defined as the positive behaviors of participants that are not recognized by formal contracts or requirements, but would lead to the effective achievement of the project goals [8]. For example, in the South-to-North Water Transfer project, a labor contest (which is a typical practice in China to motivate and improve OCB engagement in the project implement) was held by the local government and all participants in this megaproject were involved.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is rather limited literature on OCB in the context of megaprojects. Similar to the definition of OCB in organizational areas, OCB in the megaprojects field can be defined as the positive behaviors of participants that are not recognized by formal contracts or requirements, but would lead to the effective achievement of the project goals [8]. For example, in the South-to-North Water Transfer project, a labor contest (which is a typical practice in China to motivate and improve OCB engagement in the project implement) was held by the local government and all participants in this megaproject were involved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in the South-to-North Water Transfer project, a labor contest (which is a typical practice in China to motivate and improve OCB engagement in the project implement) was held by the local government and all participants in this megaproject were involved. Participants voluntarily competed in the aspects of safety, quality, schedule, innovations, environmental protections, and so on forth [8]. Participants could only win by going beyond the typical requirements and achieving high performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After a series of information transfer, task execution, resource integration, process processing, and finally, it outputs integrated products that meet the requirements. This process embodies the MIP technology integration system as a whole, and finally achieves the overall goal of MIP technology through a series of functions [7] .…”
Section: Mip Technology Integration Featuresmentioning
confidence: 99%
“…Zheng et al (2018) examined the antecedents and consequences of relational behavior of participating organizations in China's megaprojects based on the theory of planned behavior (TPB), and found that the adoption of relational behavior is equally motivated by an organization's behavioral intention and perceived behavioral control while information exchange contributes the most to achieving high quality of a project relationship. Yang et al (2018) used a quantitative cross-case study to present a framework of organizational citizen behavior (OCB) in construction megaprojects that is composed of five types of behaviors: compliance, contingent collaboration, harmonious relationship maintenance, conscientiousness, and initiative. Wang et al (2018) presented an individual-level analysis that investigates how institutional pressures impact project practitioners' organizational citizenship behaviors for the environment according to the survey data collected from China's megaprojects.…”
mentioning
confidence: 99%